ISLAMIC BOARDING SCHOOLS AS PILLARS OF TRANSFORMATIVE EDUCATION TOWARDS A GOLDEN INDONESIA - Ahmad Rausyan Fikri; Sugiono Sugiono (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Pesantren (Islamic boarding schools) are the oldest Islamic educational institutions in Indonesia and have made a significant contribution to shaping the nation's character, morality, and intellect. Amidst globalization and technological advancements, pesantren face significant challenges in transforming themselves without abandoning their traditional values. This article aims to analyze the role of pesantren as pillars of transformative education in supporting the vision of Golden Indonesia 2045, which focuses on developing superior and character-based human resources. The writing method used is a literature review and conceptual analysis of various literature on pesantren education, transformative education theory, and national education policy. The study results indicate that pesantren possess cultural, spiritual, and social strengths capable of addressing the needs of 21st-century education through the integration of Islamic values, technological innovation, and economic empowerment.